Creep Experimental Study of Rocks Containing Weak Interlayer Under Multilevel Loading and Unloading Cycles - Tang, Liming; Zhao, Yanlin; Liao, Jian; Liu, Qiang (Frontiers in Earth Science, 2020)
Using the cyclic loading and unloading method, rheological tests of intact sandstones and composite sandstones containing a weak interlayer (WI) with inclination angles 15°, 30°, 45° and 60° under different axial loading were carried out. The decay creep time, steady-state creep strain rate, instantaneous strain, viscoelastic strain, viscoplastic strain, and failure modes of sandstones and composite sandstones were studied. The influence law of stress level and WI inclination angle on the rheological properties of the rock was studied. Results indicated that: (1) the rheological failure strength of sandstone is 72%-96% of uniaxial compressive strength. (2) Whether it is intact sandstone or composite sandstone, the decay creep time at the first stress level is longer than those of other stress levels. The steady-state creep strain rate of specimens is gradually increasing from the first stress level to the last stress level. (3) At the first stress level, the proportion of creep strain to total strain is 25.3%~60.5%. Moreover, under the same axial stress level, the instantaneous strain and total strain of the rock containing WI are larger than those of intact rock. (4) With the increase of stress, the viscoplastic strain of the intact specimen decreases at low stress levels, and increases at high stress levels. And with the increase of the WI inclination angle, the instantaneous elastic strain and instantaneous plastic strain will increase. (5) The rheological failure mode of specimens changes from split tensile failure to shear failure along the interface of WI, the larger the WI inclination angle, the more obvious the shear failure.